2017
DOI: 10.1111/epi.13647
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of intravenous NAX 810‐2, a novel GalR2‐preferring analog, for anticonvulsant efficacy and pharmacokinetics

Abstract: Objective Potential clinical utility of galanin or peptidic analogs has been hindered by poor metabolic stability, lack of brain penetration, and hyperglycemia due to GalR1 receptor activation. NAX 810-2, a GalR2-preferring galanin analog, possesses 15-fold greater affinity for GalR2 over GalR1 and protects against seizures in the mouse 6 Hz, corneal kindling, and Frings audiogenic seizure models. The purpose of these studies was to further evaluate the pre-clinical efficacy and pharmacokinetics of NAX 810-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…27 The human equivalent dose of fenfluramine in these experiments was calculated, based on the proportional relationship of body surface areas, as described by Reagan-Shaw and coworkers. The median effective dose (ED 50 ) of fenfluramine and 95% confidence interval (CI) for blocking Sz at 30 minutes following the intraperitoneal injection in DBA/1 mice were calculated using Probit analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The human equivalent dose of fenfluramine in these experiments was calculated, based on the proportional relationship of body surface areas, as described by Reagan-Shaw and coworkers. The median effective dose (ED 50 ) of fenfluramine and 95% confidence interval (CI) for blocking Sz at 30 minutes following the intraperitoneal injection in DBA/1 mice were calculated using Probit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The median effective dose (ED 50 ) of fenfluramine and 95% confidence interval (CI) for blocking Sz at 30 minutes following the intraperitoneal injection in DBA/1 mice were calculated using Probit analysis. 27 The human equivalent dose of fenfluramine in these experiments was calculated, based on the proportional relationship of body surface areas, as described by Reagan-Shaw and coworkers. 28…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that this strain of mice does not survive kindling stimulation and therefore was not evaluated in this model (data not shown). By contrast, CF-1 mice are routinely used in the kindling model and demonstrate a robust and reproducible kindling acquisition rate (68,90). The reduction in mortality and post-kindling seizure burden in the kindling model suggests the potential for music-mediated disease burden and validates use of this strain for additional testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional analogs were designed and synthesized that showed preference toward GalR2 over GalR1 and still maintained metabolic stability and anticonvulsant efficacy [26]. The lead analog NAX 810-2, a GalR2-prefering anticonvulsant, was selected and has since been further evaluated for pre-clinical efficacy and safety [2729]. Both NAX 505-5 (also known as Gal-B2) and its GalR2-preferring derivative [N-Me, desSar]Gal-B2 have been recognized as pharmacological tools for studying the galanin receptors [30,31].…”
Section: Introductonmentioning
confidence: 99%